The manager's pocket guide to organizational learning - Gill, Stephen J., 1947- (Managers Pocket Guide Series., 2000)
Today's organizations are in the learning business. Employees must take in a constant supply of new information and apply it to their work regardless of their position. Organizational learning is the process of forming and applying collective knowledge to problems and needs. Organizations learn through five main activities: 1) systematic problem solving; 2) experimentation with new approaches; 3) learning from their own experience; 4) learning from the experiences and best practices of others; and 5) transferring knowledge quickly and efficiently throughout the organization. Organizational lea.